2018
DOI: 10.21037/jtd.2017.12.69
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile in primary lung cancer cells lines obtained by endobronchial ultrasound transbronchial needle aspiration

Abstract: The miRNA expression profile is feasible and reliable in EBUS-TBNA specimens. Validation of this protocol in fresh cytological specimens represents an effective and reproducible method to correlate translational and clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…LNmets were expanded in cell culture (Fig. 1A) as we previously showed[11]; morphological examination together with immunofluorescence staining using anti-pan-cytokeratin antibody (Pan-CK) confirmed their epithelial origin (Fig. 1B).…”
Section: Resultssupporting
confidence: 69%
“…LNmets were expanded in cell culture (Fig. 1A) as we previously showed[11]; morphological examination together with immunofluorescence staining using anti-pan-cytokeratin antibody (Pan-CK) confirmed their epithelial origin (Fig. 1B).…”
Section: Resultssupporting
confidence: 69%
“…Based on our previous expertise, we are developing new applications for EBUS-TBNA such as a new protocol for EBUS-TBNA primary lung cancer cell culture and microRNA profile in stage IIIA (pN2) NSCLC patients, testing the feasibility of a microRNA profile obtained from EBUS-TBNA [ 24 ] and the correlation with the prediction of chemotherapy response. In addition, new molecular analyses are being developed, and the correlation between PDL-1 expression and tumour histology is under evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…As new technological solutions are developing to improve diagnostics, the number of novel promising cancer-related markers also increases and one of these is microRNAs. MicroRNA are small, single-stranded non-coding RNA, with length of 19-25 nucleotides, which are present in biological fluids (blood, plasma, saliva, and urine) and can be tested in formalin-fixed paraffin-embedded and in fresh tissue biopsies (Freitas et al, 2021;Guarize et al, 2018;Wu et al, 2019). Recent studies showed that miRNAs play a role in the tumorigenesis by regulating the cell cycle, angiogenesis, metabolism, proliferation, metastasis, apoptosis, and gene expression via post-transcriptional regulation of mRNA.…”
Section: Micrornamentioning
confidence: 99%